Burning Money? Government Lending in a Credit Crunch - Gabriel Jiménez; José-Luis Peydró; Rafael Repullo; Jesuś Saurina (Universitat Pompeu Fabra (upf), Department of Economics and Business, 2019)
We analyze a small, new credit facility of a Spanish state-owned bank during the crisis, using its continuous credit scoring system, its firm-level scores, and the credit register. Compared to privately-owned banks, the state-owned bank faces worse applicants, (softens) tightens its credit supply to (un)observed riskier firms, and has much higher defaults, especially driven by unobserved ex-ante borrower risk. In a regression discontinuity design, the supply of public credit causes: large positive real effects to financially-constrained firms (whose relationship banks reduced substantially credit supply); crowding-in of new private-bank credit; and positive spillovers to other firms. Private returns of the credit facility are negative, while social returns are positive. Overall, our results provide evidence on the existence of significant adverse selection problems in credit markets.
Keywords: E44; G01; G21; G28; 330; adverse selection; state-owned banks; credit crunch; real effects of public credit; crowding-in